PERANCANGAN PROFIL NAGARI TALANG BABUNGO DALAM BENTUK FILM DOKUMENTER - YUDI NOFENDRA, Dini Faisal, S.Ds., M.Ds., Hendra Afriwan, S.Sn. M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Talang Babungo has the advantages of various potentials, natural and cultural wealth. However, the effective information media is not optimal to inform the area, so information on the film media profile of Talang Babungo is very much needed for the benefit of the general public and in the regions.The purpose of the design of the documentary film profile of Talang Babungo describes history, culture, agriculture, education, social and economics as the main media design in addition to other supporting media.The design methodology uses the glass box method. This method is a method of rational, objective and systematic thinking to logically examine things and be free from irrational thoughts and considerations. Metode data analysis were used that approach 5w + 1h that is what (what), who (who), when (when), where (in which), why (why) and how (how) are used as concepts in problem solving, the findings of the design produce films documentary Talang Babungo profile in the form of information and communication media.Keywords: Profile, Documentary film, Talang Babungo